DNA-based nanowires and nanodevices. Issue 1 (2nd January 2017) - Ram Kumar Pandian, Sureshbabu; Yuan, Chiun-Jye; Lin, Chung-Ching; Wang, Wen-Hung; Chang, Chia-Ching
Abstract: DNA (deoxyribonucleic acid) is a highly versatile biopolymer that has been a recent focus in the field of nanomachines and nanoelectronics. DNA exhibits many properties, such as high stability, adjustable conductance, vast information storage, self-organising capability and programmability, making it an ideal material in the applications of nanodevices, nanoelectronics and molecular computing. Even though native DNA has low conductance, it can easily be converted into a potential conductor by doping metal ions into the base pairs. Nickel ions have been employed to tune DNA into conducting polymers. Doping of nickel ions within DNA (Ni-DNA) increases the conductivity of DNA by at least 20 folds compared with that of native DNA. Further studies showed that Ni-DNA nanowires exhibit characteristics of memristors, making them a potential mass information storage system. In summary, DNA molecules have promising applications in a variety of fields, including nanodevices, nanomachines, nanoelectronics, organic solar cells, organic light emitting diodes and biosensors. Abstract :